Ethical Issue Related to ‘Save the Life of the Patient’ at Mthatha General Hospital in South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Resuscitation of a patient with life threatening conditions, before referral to another department or hospital, is a legal obligation on the part of the health professionals. Several deaths occur every year in hospitals and health care centres without an emergency management. Objective: To highlight the ethical issue related to ‘Save the Life of the Patient’ at Mthatha hospital in South Africa. Case History: This is the case (AM) report of a 16-year-old Grade 10 learner who was assaulted physically as well as sexually. She was bleeding from a stab wound to her when she was brought to the Mthatha General Hospital’s (MGH) casualty. She was then referred to the Bedford hospital for repair of the tendon of her right wrist as recommended by the doctor on duty. The patient was referred to Sinawe Centre for forensic management, where she collapsed during an interview. The patient was taken on a stretcher to the MGH casualty for an emergency treatment of her blood pressure. The history of the patient and the care duty of the health professionals are discussed. Ethical issues are also highlighted in relation to the ‘preserve the life first’ principle in this case report. Conclusion: There was a serious breach in duty of care by medical officers in the Mthatha hospital, South Africa. It is an ethical priority to save the life of the patient.